3(3x+1)=3(5x-3)

Simple and best practice solution for 3(3x+1)=3(5x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x+1)=3(5x-3) equation:


Simplifying
3(3x + 1) = 3(5x + -3)

Reorder the terms:
3(1 + 3x) = 3(5x + -3)
(1 * 3 + 3x * 3) = 3(5x + -3)
(3 + 9x) = 3(5x + -3)

Reorder the terms:
3 + 9x = 3(-3 + 5x)
3 + 9x = (-3 * 3 + 5x * 3)
3 + 9x = (-9 + 15x)

Solving
3 + 9x = -9 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
3 + 9x + -15x = -9 + 15x + -15x

Combine like terms: 9x + -15x = -6x
3 + -6x = -9 + 15x + -15x

Combine like terms: 15x + -15x = 0
3 + -6x = -9 + 0
3 + -6x = -9

Add '-3' to each side of the equation.
3 + -3 + -6x = -9 + -3

Combine like terms: 3 + -3 = 0
0 + -6x = -9 + -3
-6x = -9 + -3

Combine like terms: -9 + -3 = -12
-6x = -12

Divide each side by '-6'.
x = 2

Simplifying
x = 2

See similar equations:

| 3*10+4*y=12 | | x(x-1)/2=45 | | Sinx-cos^2x=0 | | 15=16x | | 3*5+4*y=12 | | 2x+37=19x-35 | | (11-2^2)/(3*2^2) | | -5n-9=-54 | | 3*-5+4*y=12 | | x+6y^2=8 | | 3*-10+4*y=12 | | x+17+3x+1=90 | | (4x+17)=(5x-1) | | x^2-86x+1320=0 | | 3X^3=15 | | (3)(12)+8x=86 | | 16+8y=12y | | 3*-14+4*y=12 | | 4(5x+3)=28 | | x-45+150=180 | | -4x-1/3=35/3 | | x+4+132=180 | | (3y+8)=(6y-1) | | 4x-1/3=35/3 | | 6x+(2)(15)=150 | | -5y+6=-7y-14 | | (6x)=(5x+9) | | 8y-3=5(y+6) | | 3x-20=6x-8 | | 10+3y=-6 | | S=Ngj | | 3(2+x)=-36 |

Equations solver categories